Implementation of early rehabilitation for critically ill children in China: A survey and narrative review of the literature - Zhang, Ting; Duan, Xiaoling; Feng, Ying; Jiang, Wei; Hou, Xueqin; Liu, Ling; Huang, Qinrong; Tang, Xiang; Lin, Li; Zhang, Mingqiang; Tao, Liang; Liu, Guoqing; et al. (Frontiers in Pediatrics, 2022)
Introduction: The focus of this survey was to understand the current status of implementation of early rehabilitation for critically ill children in China. We also reviewed the available literature on this topic for further insights to inform its future development. Materials and Methods: We used a cross-sectional study design to survey tertiary hospitals nationwide. Questionnaires were distributed via the social media platform ‘WeChat Questionnaire Star’ within the framework of the Rehabilitation Group of the Pediatrics Branch of the Chinese Medical Association. A narrative literature review on the implementation of the early rehabilitation for critically ill pediatric and/or adult patients was carried out. Results: A total of 202 valid questionnaires were received. About half (n=105, 52.0%) of respondent hospitals reported that they implement early rehabilitation for critically ill children. Among these 105 hospitals, 28 implemented a continuous chain of early rehabilitation. A total of 24 hospitals had set up permanent specialized centralized early rehabilitation units for critically ill children. Implications and Future Directions: Early rehabilitation for critically ill children is not widely available in China and only a minority of hospitals implement a continuous chain of early rehabilitation. To improve this undesirable situation, we suggest creating a two-level integrated system comprising centralized early rehabilitation units and surrounding early rehabilitation networks within a region.